Absceso epidural espinal. Presentación de un caso clínico - Vázquez, A; Portillo, E; Guridi, J; Gallo-Ruiz, A; Azcona, J; Zazpe, I; Olier, J (Anales del Sistema Sanitario de Navarra, 2009)
Este artículo no tiene resumen